Emergency medical technician : - Aehlert, Barbara (McGraw Hill, 2009)
EMTs are often the first licensed EMS personnel to arrive on the scene of an emergency, size up the situation, and provide emergency care and transportation. They practice in a wide diversity of settings—EMTs are everywhere in our community, many of them